Architecture Diversity in The Indonesian Coastal Area Due to Cultural Acculturation - Muchlisiniyati Safeyah; Eva Elviana (Nusantara Science and Technology Proceedings, 2020)
This study aims to identify architecture in coastal areas that are influenced by acculturation. Indonesia is the second country with the longest coastal area in the world. Coastal areas are un-secluded areas that have the potential to open up access to economic, social, and cultural factors. The wide-open cultural access causes the coastal areas to have diversity in architecture, Cultural acculturation is a process of cultural fusion as a result of blending immigrants culture with the local culture. The architecture of the coastal area has specific characteristics with several forms of amalgamation from immigrant culture's influence. Using a qualitative approach with the literature study method. The diversity of architecture in Indonesia's coastal areas includes traditional architecture, modern and contemporary architecture. According to historical records, most of the immigrants who entered Indonesia through various coastal areas were ethnic Chinese, Arabs, and Dutch. The culture of the immigrants is mixed with the culture of the local community. In its development, the mixture of cultures from China, Arabic, and the Netherlands gave a significant influence on the architecture of coastal communities. The mixing of cultures is manifested in various values ??and forms in the figure and form of the architecture. Chinese architecture, Arabic architecture, and Colonial architecture are forms of cultural acculturation.